ANALISIS PENGARUH BEBAN KERJA, STRES KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS BANK SYARIAH INDONESIA KC JEMBER SUDIRMAN - Arsita, Selly; Suharto, Akhmad; Puspitadewi S, Ira (Growth, 2024)
Activities in the world of work, especially in the banking sector, where banking development must continue to develop every year, causing intense competition in achieving organizational goals. To gain a competitive advantage. It is very important to achieve management efficiency by improving human resources and improving employee performance in the organization. To further increase productivity, PT Bank Syariah Indonesia also increases employee performance which can be improved in various ways, including by instilling an optimal work culture that influences work behavior so that it will increase individual job satisfaction and the productivity of the unit itself which will ultimately influence employee performance. the company as a whole. The purpose of this research is to determine and analyze the influence of workload, work stress, and work environment on the performance of BSI KC Jember employees. This type of research is causality research. The population in this research is BSI KC Jember employees. The sample used was 55 respondents using probability sampling techniques. The analysis tool uses multiple linear regression. The research results prove that workload, work stress, and work environment have a significant effect on the performance of BSI KC Jember employees.